CHOOSING THE BEST SPORTS SHOES FOR RUNNING (Physical Culture and Sport: Scientific Perspective, 2023)
The article is devoted to the analysis of existing sports shoes for running, on the basis of which the optimal designs were selected to ensure the functionality of the shoes not only from an aesthetic point of view, but also from the point of view of protecting the foot from injuries and negative external influences.The article reviews various types of sports shoes for running. The scientific and methodological literature on modern approaches to researching the design of sports shoes for running is analyzed, including: the design of the shoe upper, the type of sole, materials, the method of fastening, and the features of the insole.Along with the positive aspects of using sports shoes for running, the article focuses on the existing limitations and shortcomings. In particular, the problem of injuries during running due to improper choice of sports shoes is considered. The proportion of lower limb running injuries by gender, anatomical location and specific pathology is considered. The relation between running injury and static lower limb alignment in recreational runners is analyzed. The incidence and distribution of stress fractures in competitive track and field athletes was analyzed.In addition, the authors of the article suggest possible optimal sports shoes for running, taking into account the current market of sports goods available in our country. The article emphasizes the importance of further research to improve the efficiency of sports shoes, comfort and safety.By analyzing various aspects of running shoes, this article provides readers with generalized information about these products and contributes to the understanding of their impact on sports. It can be useful for coaches, physical therapists, athletes, and anyone interested in comfort and safety during recreational and training running.
Keywords: sports shoes; running shoes; sneakers; running; injury; comfort